Introducing Feedforward: Renaming and Reframing Our Repertoire for Written Response - Sheri Rysdam; Lisa Johnson-Shull (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Categorizing instructor comments on student drafts leads writing center researchers to argue for the need to reframe our professional discussion on instructor response, based on the concept of “feedforward.”